Anarchism and the Anti-Colonial Canarian Imagination: the Missing Flag - Galván-Álvarez, Enrique (Oxford Academic, 2024)
This paper explores the under-represented political experience of Canarians in transatlantic networks of anti-authoritarian and anti-colonial resistance in the late nineteenth century. Much of the relevant historiographic literature, both in English and in Spanish, treats the Canary Islands as an integral part of mainland Spain. This obscures the colonial history of the Islands and the subaltern position of Canarians in Spanish imperial and racial hierarchies. In order to counterbalance this absence, I discuss the life and writings of Secundino Delgado (1867–1912), a Canarian who travelled across North, Central and South America and became involved in a number of interconnected struggles: labour rights, anarchism, and Cuban and Canarian independence movements. Delgado’s peculiarly in-between consciousness resonated with that of other Canarians and Canarian-descendants who had joined liberation struggles against Spanish imperialism across the Americas. As the first Canarian thinker to articulate a national consciousness which is also decidedly libertarian and anti-colonial, Delgado offers valuable insights into the singular history of the Canaries, their place in the transatlantic networks of resistance of the eighteenth and nineteenth centuries and anti-colonial anarchism at large.
Keywords: Histories of Radicalism; anarchism; anti-colonial canarian; flag; Scopus